Pengaruh Harga Lokasi Fasilitas Dan Promosi Terhadap Kepuasan Konsumen Pada Perumahan Villa Pertiwi - Rizli Muktar Nst, Nurul Adwiya, Hayanuddin Safri, Daslan Simajuntak, Meisa Fitri Nasution (Journal Economy and Currency Study (JECS), 2021)
The purpose of this study was to determine the effect of price, location, facilities and promotions on consumer satisfaction at Villa Pertiwi housing either partially or simultaneously. Data collection using interviews, questionnaires and literature study. Work on data analysis methods using the help of SPSS 16.0 for Windows software. This study used a sample of 40 employees who were drawn using census techniques. The results of the research based on the test simultaneously (F test) show that simultaneously (simultaneously) price (X1), location (X2) facilities (X3) and promotion (X4) have an effect on customer satisfaction (Y) Housing Villa Pertiwi, where the value of Fcount (477,687) > Ftable (2.63) with a probability of 0.000 < 0.05. The results of partial hypothesis testing (t test) show that price (X1) has a positive and significant effect on customer satisfaction (Y) at Villa Pertiwi Housing where tcount (6.149) > ttable (1.689) with a probability of 0.000 < 0.05; location (X2) has a positive and significant effect on customer satisfaction (Y) Housing Villa Pertiwi., where the value of tcount (8.728) > ttable (1.689) with a probability of 0.000 < 0.05; Facility (X3) has a positive and significant effect on customer satisfaction (Y) in Villa Pertiwi Housing, where the value of tcount (21.980) > ttable (1.689) with a probability of 0.001 < 0.05. promotion (X4) has a positive and significant effect on customer satisfaction (Y) in Villa Pertiwi Housing, where the value of tcount (2.095) > ttable (1.689) with a probability of 0.001 < 0.05. The value of Adjusted R Square shows that customer satisfaction can be explained by price, location, facilities and promotions, while the remaining 2.0% can be explained by other factors not examined in this study.